2016
DOI: 10.1007/s10517-016-3174-z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Properties of Modified Detonation Nanodiamonds and Sorbed Doxorubicin on the Model of Ehrlich Ascites Carcinoma

Abstract: We studied antitumor properties of modified detonation nanodiamonds loaded with doxorubicin on in vivo model of Ehrlich ascites carcinoma. The type of tumor development and morphological characteristics of the liver, kidneys, and spleen were evaluated in experimental animals. Modified nanodiamonds injected intraperitoneally produced no antitumor effect on Ehrlich carcinoma. However, doxorubicin did not lose antitumor activity after sorption on modified nanodiamonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…In this study, we used modified detonation NDs (MNDs), which have good colloidal stability in water suspensions and can be used in biological and medical studies [26][27][28]. MNDs were prepared from commercial detonation NDs (Real-Dzerzhinsk Ltd, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used modified detonation NDs (MNDs), which have good colloidal stability in water suspensions and can be used in biological and medical studies [26][27][28]. MNDs were prepared from commercial detonation NDs (Real-Dzerzhinsk Ltd, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of Ti/NCD composites will further improve its performance and expand its application range, for example, the lubrication of artificial joints for medical surgery [ 129 , 130 , 131 , 132 ]. Due to the biocompatibility of both NCD and Ti [ 34 , 135 , 136 ], Chen et al [ 60 ] demonstrated that a novel two-dimensional (2D) diamond nanosheet coating on Ti alloys synergistically enhances friction and wear performance combined with natural silk fibroin.…”
Section: Ncd For Tribological Applicationsmentioning
confidence: 99%
“…It was also found that DOX does not lose its activity after being absorbed on the ND surface (Medvedeva, Zhukov, Inzhevatkin, & Bezzabotnov, 2016). ND-PEG-DOX nanocomposites were used to provide a slow and sustained release of DOX, which was desirable in chemotherapy for the prolonged and continuous release of antitumor drugs (Wang et al, 2013).…”
Section: Drug Deliverymentioning
confidence: 99%